Overexpression of GPR41 attenuated glucose production in propionate-induced bovine hepatocytes - Lin, Miao; Jiang, Maocheng; Yang, Tianyu; Zhao, Guoqi; Zhan, Kang (Frontiers in Veterinary Science, 2022)
Bovine liver mainly utilizes the propionate as a gluconeogenic substrate to synthesize the glucose. However, the mechanism underlying the regulatory effects of propionate on the glucose production in bovine hepatocytes remains less known. Previous studies have demonstrated G protein-coupled receptor 41 (GPR41) as receptors for propionate. We hypothesized that propionate may regulate the glucose production by GPR41 in bovine hepatocytes. Therefore, the aim of study was to investigate the regulatory effects of propionate and GPR41 on glucose production in bovine hepatocytes. These results showed that expression of phosphoenolpyruvate carboxykinase 2 (PCK2) and pyruvate carboxylase (PC) genes involved in the gluconeogenesis were significantly enhanced with propionate treatment. Remarkably, addition of propionate promotes the glucose production in bovine hepatocytes. Expression of GPR41 was increased by addition of propionate in bovine hepatocytes overexpressed GPR41 by AAV1 compared with absence of propionate. Interestingly, expression of PCK2 was markedly attenuated in GPR41 overexpressed-hepatocytes with propionate. Importantly, overexpression of GPR41 attenuated glucose output in propionate-induced bovine hepatocytes. These findings revealed that GPR41 negatively regulates glucose production by downregulating the expression of PCK2 in propionate-induced bovine hepatocytes.